Analysis of the Innovative Applications of the Traditional Bamboo Material and Related Technology in Architectural Design - Tang, Zirong (Transactions on Social Science, Education and Humanities Research, 2023)
Bamboo, a kind of natural, fast-growing material with a similar texture to wood, is very abundant in China. The rational development and utilization of bamboo materials can alleviate the domestic wood supply pressure, and has very important economic, social and ecological advantages. At the same time, bamboo is more environmentally friendly, which absorbs four times more carbon dioxide than ordinary trees. It has machining performance of turning, milling and cutting during machining. And it can be fully recycled after using. Bamboo is also a low-energy building material. If the building area is equal, the energy consumption of bamboo and concrete is 1:8, while that of steel is 1:50. The special cultural importance of bamboo also cannot be ignored. With the rapid development of modern industrialization, people living in concrete structure jungles are eager to return to nature. The 21st century is a fusion of nature and architecture.